2021
DOI: 10.1180/clm.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal stability and adsorption performance of MIL-53(Fe)@montmorillonite

Abstract: This is a 'preproof' accepted article for Clay Minerals. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…163 In order to enhance the chemical stability and mechanical strength of MOFs and prevent the leaching of iron ions, MOFs can be loaded on other materials such as montmorillonite, cellulose nanomaterial composites (CNM), polyaniline, hydrogel composites, and SiO 2 . 171–175 Dai et al 171 synthesized an eco-friendly clay-based adsorbent (MIL-53(Fe)@Mnt) by using an in situ growth technique to grow MIL-53(Fe) on the surface of montmorillonite (Mnt) nanospheres. The results showed that MIL-53(Fe)@Mnt exhibited good adsorption capacity for MB and remained stable at the end of the experiment.…”
Section: Iron (Hydr)oxidesmentioning
confidence: 99%
“…163 In order to enhance the chemical stability and mechanical strength of MOFs and prevent the leaching of iron ions, MOFs can be loaded on other materials such as montmorillonite, cellulose nanomaterial composites (CNM), polyaniline, hydrogel composites, and SiO 2 . 171–175 Dai et al 171 synthesized an eco-friendly clay-based adsorbent (MIL-53(Fe)@Mnt) by using an in situ growth technique to grow MIL-53(Fe) on the surface of montmorillonite (Mnt) nanospheres. The results showed that MIL-53(Fe)@Mnt exhibited good adsorption capacity for MB and remained stable at the end of the experiment.…”
Section: Iron (Hydr)oxidesmentioning
confidence: 99%
“…For example, Pb 2+ can be adsorbed by montmorillonite, kaolinite, sepiolite, attapulgite, illite, rectorite, and bentonite (Tang et al, 1981;Zhang, 2012;Lai, 2013), and Cu 2+ can be adsorbed by sepiolite, kaolinite, illite, bentonite, and montmorillonite (Koppelman et al, 1977;He et al, 2000;Khosravi et al, 2016;Cecilia et al, 2017;Chen, 2017).. In addition, numerous synthetic adsorbents have been developed to remove heavy metal toxins and organic pollutants from wastewater (Dai et al, 2021;Wang et al, 2022). Examples of these include the hybrid adsorbent PANI@KG for water treatment (Ouis et al, 2022) and activated carbon based on prickly pear seeds and a conductive polymer matrix based on polyaniline for the removal of https://doi.org/10.1180/clm.2022.20 Published online by Cambridge University Press anionic Congo red dye from aqueous solutions (Lahreche et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Porous nanoarchitectures based on clay minerals have been a focus of growing interest in the field of materials science due to their ability to produce nanostructures with beneficial functional and structural properties (Polverejan et al , 2000; Ruiz-Hitzky & Aranda, 2014; Kooli et al , 2017). This multifunctionality supports their use in various fields, notably in environmental remediation via the removal of pollutants due to their catalytic and adsorption properties and in the medical field in terms of the development of viable and functional biodevices for biomedical applications, as supports for the controlled release of drugs and in bioimaging (Tobajas et al ., 2017; Akkari et al , 2018; Yuan et al ., 2018; Yang et al ., 2019; Dai et al , 2021; Persano et al , 2021).…”
mentioning
confidence: 99%